CONSTRUCTED WETLANDS TO TREAT HOUSE WASTEWATER. A SOLUTION FOR INDONESIA? - Denny Kurniadie (Direktorat Sumber Daya Akademik dan Perpustakaan, 2001)
A pilot project of one constructed subsurface flow wetlands to treat sewage fromfamily Subandi house has been built in Bandung Indonesian in February 1999.The water samples from both influent and effluent (COD, BOD5, NO3-N, NO2-N, NH4-N, PO4-P, pH, and settleable solids, and O2) were taken twice a month and analyzed. Fecal coliforms bacteria was determined by MPN method. Theobjective of this study was to install one constructed subsurface flow wetlandswith vertical flow to treat sewage from private house. The treatment efficiencyof this constructed wetlands was already relatively high, although this constructed wetlands was just only eleven months in operation. The results were very promising and give a possibility of constructed wetlands to be installed anddeveloped in tropical countries, especially in Indonesia, as a viable alternative to conventional wastewater technology, because this system is and simple and cost effective.Keywords: Constructed wetlands, wastewater treatment, conventional system, subsurface flow